Effects of scale worm parasitism on interactions between the symbiotic gill microbiome and gene regulation in deep sea mussel hosts - Yao, Gaoyou; Zhang, Hua; Xiong, Panpan; Jia, Huixia; He, Maoxian (Frontiers in Microbiology, 2022)
Diverse adaptations to the challenging deep sea environment are expected to be found across all deep sea organisms. Scale worms Branchipolynoe pettiboneaeis are believed to adapt to the deep sea environment by parasitizing deep sea mussels; this biotic interaction is one of most known in the deep sea chemosynthetic ecosystem. However, the mechanisms underlying the effects of scale worm parasitism on hosts are unclear. Previous studies have revealed that the microbiota plays an important role in host adaptability. Here, we compared gill-microbiota, gene expression and host-microorganism interactions in a group of deep sea mussels (Gigantidas haimaensis) parasitized by scale worm (PA group ) and a no parasitic control group (NPA group). The symbiotic microorganism diversity of the PA group significantly decreased than NPA group, while the relative abundance of chemoautotrophic symbiotic bacteria that provide the host with organic carbon compounds significantly increased in PA. Interestingly, RNA-seq revealed that Gigantidas haimaensis hosts responded to B. pettiboneaeis parasitism through significant upregulation of protein and lipid anabolism related genes , and that this parasitism may enhance host mussel nutrient anabolism but inhibit the host’s ability to absorb nutrients, thus potentially helping the parasite obtain nutrients from the host. In an integrated analysis of the interactions between changes in the microbiota and host gene dysregulation, we found an agreement between the microbiota and transcriptomic responses to B. pettiboneaeis parasitism. Together, our findings provide new insights into the effects of parasite scale worms on changes in symbiotic bacteria and gene expression in deep sea mussel hosts. We explored the potential role of host-microorganism interactions between scale worms and deep sea mussels, and revealed the mechanisms through which scale worm parasitism affects hosts in deep sea chemosynthetic ecosystem.